Adipocyte-derived Periostin mediates glucocorticoid-induced hepatosteatosis in mice - Jian Wan; Yi Shan; Xi Song; Song Chen; Xinyuan Lu; Jie Jin; Qing Su; Bin Liu; Wanju Sun; Bo Li (Elsevier, 2020)
Objective: Long-term glucocorticoids (GCs) therapy usually causes many metabolic side effects, including fatty liver. However, the molecular mechanisms remain poorly understood. Herein, we explored the molecular basis of GCs in the development of fatty liver. Methods: C57BL/6 male mice were injected with Dexamethasone (DEX) while mouse primary hepatocytes (MPHs), HepG2 and Hep1-6 cells were cultured in the presence of DEX. Genes expression in liver tissues and hepatocytes were assessed by quantitative real-time PCR and western blotting, respectively. To explore whether Periostin is involved in the development of GCs-induced fatty liver, wild-type and Periostin knockout mice were treated with DEX or vehicle control. Luciferase reporter and chromatin immunoprecipitation assays were used to determine the regulatory roles of GCs on Periostin expression. Results: We show that treatment of dexamethasone (DEX), a synthetic analog of GCs, led to the accumulation of triglycerides in the livers of mice, but not in cultured hepatocytes, suggesting that GCs may promote liver steatosis through integrative organ crosstalk mediated by systemic factors. We further found that DEX upregulated the expression levels of Periostin in white adipose tissues, which in turn promoted liver steatosis. Administration of a Periostin-neutralizing antibody or genetic ablation of Periostin largely attenuated DEX-induced hepatic steatosis in mice. Conclusions: Our findings provided a novel insight that GCs could promote liver steatosis through integrative organ crosstalk mediated by white fat-secreted Periostin. These results establish Periostin as an endocrine factor with therapeutic potential for the treatment of GCs-associated fatty liver. Keywords: Periostin, Glucocorticoid, Fatty liver, Adipocyte, Hyperglycemia